Can socioeconomic factors explain geographic variation in overweight in Norway? - Jonas Minet Kinge; Ólöf Anna Steingrímsdóttir; Bjørn Heine Strand; Øystein Kravdal (Elsevier, 2016)
We explore if the geographic variation in excess body-mass in Norway can be explained by socioeconomic status, as this has consequences for public policy. The analysis was based on individual height and weight for 198,311 Norwegian youth in 2011, 2012 and 2013, stemming from a compulsory screening for military service, which covers the whole population aged seventeen. These data were merged with municipality-level socioeconomic status (SES) variables and we estimated both ecological models and two-level models with a random term at the municipality level. Overweight was negatively associated with income, education and occupation at municipality level. Furthermore, the municipality-level variance in overweight was reduced by 57% in females and 40% in males, when SES factors were taken into account. This suggests that successful interventions aimed at reducing socioeconomic variation in overweight will also contribute to reducing the geographic variation in overweight, especially in females. Keywords: Overweight, Body mass index, Socioeconomic factors, Neighborhood, Multilevel modeling, Geographic factors, Norway